The Implementation of Authentic Assessment in Contextual Approach in Civics Education at a Junior High School in Malang Regency - Suhartono, Edi; Ediyanto, Ediyanto; Atmoko, Adi (Journal of Posthumanism, 2025)
This research examines the implementation of authentic assessment within a contextual approach in Civics Education at a Junior High School in Malang Regency. The contextual approach consists of seven components: (a) constructivism, (b) inquiry, (c) questioning, (d) learning community, (e) modeling, (f) reflection, and (g) authentic assessment. This study focuses on the seventh component. Using a qualitative case study approach, data were collected through observations, interviews, documentation studies, and literature reviews. The subjects include eighth-grade students, the Civics teacher, and the deputy head of curriculum affairs. Data analysis follows Miles and Huberman’s interactive method, with validation through source triangulation. Findings show that the school applies a contextual approach, integrating authentic assessment through performance, attitude, essay-based written, project, product, portfolio, and self-assessments.